A new pma1 mutation identified in a chronologically long‐lived fission yeast mutant. Issue 1 (28th September 2014) - Naito, Chikako; Ito, Hirokazu; Oshiro, Tomoko; Ohtsuka, Hokuto; Murakami, Hiroshi; Aiba, Hirofumi
Abstract : We isolated a chronologically long‐lived mutant of Schizosaccharomyces pombe and found a new mutation in pma1 + that encoded for an essential P‐type proton ATPase. An Asp‐138 to Asn mutation resulted in reduced Pma1 activity, concomitant with an increase in the chronological lifespan of this fission yeast. This study corroborates our previous report indicating Pma1 activity is crucial for the determination of life span of fission yeast, and offers information for better understanding of the enzyme, Pma1. Abstract : We isolated a chronologically long‐lived mutant of S. pombe . We identified one mutation in pma1 + gene that encoded for an essential P‐type proton ATPase. The identified Asp‐138 to Asn mutation resulted in reduced Pma1 activity. This was concomitant with an increase in the chronological lifespan of S. pombe .